(untitled) (E Global Congress, 2025)
Prevention of refractive errors in children requires a comprehensive approach, including hardware methods for stimulating accommodation, specialized optical correction and educational programs. This study evaluates the effectiveness of an interdisciplinary approach to the prevention of refractive errors in preschool children. The results demonstrate a significant decrease in the rate of myopia progression, improvement of the accommodative function and a decrease in visual discomfort in children who received comprehensive preventive measures.